Impact of COVID-19 pandemic in safe abortion and safe motherhood services in provincial hospital of rural Nepal: comparison of 3 waves of COVID-19 - Dangal, Binod; Basnet, Manisha; Chase, Hannah; KC, Archana; Dangol, Deeb Shrestha (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: The COVID-19 pandemic has challenged the whole world with a major public health crisis, both directly due to the disease and indirectly in all dimensions of the health care system. This included safe abortion services and safe motherhood services but data quantifying this in a lower resource setting is lacking. This study analyzed the trends of safe abortion services, post abortion contraception opted during pandemic and safe motherhood services at a provincial hospital in rural Nepal during 25 months of COVID-19 pandemic, comparing data of three major waves. Method: This is a retrospective observational study conducted at Pashupati Chaulagain Memorial Hospital. The data were collected from records of abortion and safe motherhood service registers. We compared the overall trends of safe abortion, family planning and safe motherhood services during first, second and third waves of COVID-19 pandemic and analyzed the sociodemographic profile of patients. Data analysis was done using SPSS 25 version. Result: During the study period from February 2020 to February 2022, a total of 634 and 2054 clients received safe abortion services and safe motherhood services respectively. There were reductions in clients visiting for safe abortion services during lockdown periods of first and second waves, but no differences noted during the third wave. More numbers of women opted for condoms as a family planning method during lockdown period of first and second waves with less intake of Long Acting Reversible Contraceptives and permanent methods compared to non-lockdown period. Conclusion: Utilization of safe abortion services was seriously affected in the first two waves due to COVID-19 pandemic presumably due to lockdowns, travel restrictions, home isolation, patient fear of going to hospitals, and health facilities prioritizing only COVID-19 and other emergencies. However, there was no impact in third wave for reproductive and safe motherhood services.